Diseño a nivel laboratorio de un proceso de ósmosis inversa para disminuir bario de las aguas de producción y captación del campo Cantagallo (2014)
In this work we designed a prototype laboratory scale reverse osmosis in order to decrease the concentration of barium in the water production and groundwater Cantagallo field. We performed a decision matrix allowed to choose the filter media to present some features similar to a reverse osmosis. The prototype is sketched in SketchUp program was modeled in SolidWorks software and the process was simulated with the Flow simulation tool. The pre-experiment was conducted with using water easy mounting two and three different points of the treatment plant, in two stages, first to identify the membrane efficiency and process variables, the second to apply the selected variables, and identify the proportion of removal.